An Exploration of Dual Identity in Gene Luen Yang's 'American Born Chinese’ - Putra, Jonathan Syah; Sharenlie, Grania; Djohan, Febrina Stevani; Surya, Michaella Isabel; Supriadi, Ben Othniel; Wijaya, Josh Fitzkioshi; Nathanael, Jeshua (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2024)
This study aims at investigating the challenges of being a double minority and the impact of societal expectations on their sense of self in Gene Luen Yang's graphic novel,